Exploring Social Media and Online Communication Use by Direct-to-Consumer Agricultural Businesses in Upstate New York - Katerina Weingarten; Quisto Settle; Linnea Harvey; Dwayne Cartmell (Journal of Applied Communications, 2023)
The popularization of social media and an increased interest in local food has led to the need for an online presence of direct-to-consumer agricultural producers. The COVID-19 pandemic quickly pushed the transition from traditional marketing practices to digital marketing practices, further emphasizing the importance of an online presence for small businesses. To better understand the perceptions of direct-to-consumer agricultural businesses, this study sought to understand the current use of social media and online communication and the challenges faced, related to social media and online communication, among these producers. Ten direct-to-consumer agricultural business personnel were interviewed to examine their social media and online communication use. Direct-to-consumer agricultural businesses are using Facebook as a primary social media platform and finding time to focus on social media and online communication is a challenge for agricultural personnel. A website is important to direct-to-consumer agricultural businesses, however many do not currently have a website. Direct-to-consumer agricultural businesses believe social media and an online communication are important to the growth and success of the business and are interested in educational materials and professional support to improve their online presence.
Keywords: digital media marketing; online communication; qualitative interviews; diffusion of innovations; direct-to-consumer marketing